(untitled) (Raparin Journal of Humanities (RJH), 2024)
Illegal immigration is one of the long-term and complex problems between Turkey and EU countries. Turkey always been one of the countries because of the historical background of the Ottoman Empire, has been able to resist the dominance of other countries. Turkey with one of the world’s strongest economies, has become an obstacle to the European Union, turkey’s geopolitical and geostrategic position has made it a regional and international country. It means that part of its success and the political games he plays derived from all its different poles. After Turkey’s disappointment with membership in the European Union, and after the rapid changes in the regional equation, especially after the events of the Arab Spring, collapse of the entire political and security system in part of the Middle East, particularly Syria and Iraq, Turkey embraced a new strategy for self-protection and spreading its hegemony. In this regard, the issue of migrants was one of the biggest card of Turkey towards the European Union. However, this issue in several occasions put on the dialogue table. This research is an attempt to introduce the issue of migrants and the refugee agreement between Turkey and the European Union. We will present an assessment of the 2016 Migrant Agreement and the outcome of the agreement.